Decoding Environmental Politics: Industrialization, Indigenous Rights and Resistance Movements in India - Biswal , Debendra Kumar (South Asian Journal of Social Sciences and Humanities, 2021)
Purpose of the study: To critically examine global discourse of development and it’s  dismissive of indigenous environmental knowledge and role of international indigenism in  giving space for debate on environmental politics. Based on case study of anti-POSCO  movement in Odisha in India, it has tried to sort out dichotomy of openness to change in  quality of life of local communities versus role of reactionary forces restricting development. Methodology: This study is a qualitative anthropological study among the tribal and local  communities displaced in three villages by the POSCO project in Odisha. Modernisation  theory of development was critically examined through the use of both primary and  secondary data; interview, observation, Focus Group Discussion of the community, policy  makers and activists and content analysis.Main findings: In India, modernization theory of development has pushed to the debate on  the way of development “development from below” versus “development from above”. The  anti-POSCO movement in Odisha reveals politics of truth; it’s just an extension of other  popular movements and anti-development. The truth is of double edged, a confrontation of  law of land versus rights of the people, and displacement of a section of population vs.  development. Applications of this study: This paper will help create positive hypothesis that the legal  industrialization can be legalised for the sake of poverty eradication and livelihood promotion  governance. Industrialization is not hegemony of developed countries rather relevance for  economic growth and reduction of poverty to meet MDGs in underdeveloped ones. Originality of this study: The theoretical issues raised are inter-disciplinary, pure economics  of industry and economic growth, anthropology of modernization and philosophy of social  facts and truth. It has also critically correlated the socio-cultural, environmental and  agricultural basis of protest to industrialization. The methodology is fieldwork-based observation, interview and focus group discussion. Results have been analysed through  dependent and independent variables in ecological anthropology.
Keywords: Development discourse; Environmental Politics; Indigeneity; Industrialization; Politics of Truth